Tumor-infiltrating CD4+ CD25+ FOXP3+ Treg is associated with plasma EBV DNA and disease progression in nasopharyngeal carcinoma - Enzi Feng; Yaoyu Yang; Jie Yang; Rongyi Hu; Ling Tian; Xinyu Yang; Meng Yang; Qianqian Qu; Yanxin Ren; Xiaojiang Li (Infectious Agents and Cancer)
Abstract Background Regulatory T cells (Tregs) play a significant role in immune evasion within the tumor microenvironment (TME). Nasopharyngeal carcinoma (NPC) is strongly associated with Epstein-Barr virus (EBV) infection. Previous studies have shown that EBV can suppress immune activity. The relationship between plasma EBV DNA levels and Treg infiltration in NPC remains to be elucidated. Some studies have shown that FOXP3, a Treg marker, is a favorable prognostic factor in NPC. However, relying solely on FOXP3 for Treg identification may be unreliable due to its expression in other cell types. Therefore, this study investigated the impact of tumor-infiltrating Tregs identified by CD4, CD25, and FOXP3 triple markers in NPC and the relationship between these Tregs and EBV infection. Methods In this study, 103 NPC patients were included. All tumor slides were stained using multi-immunofluorescence with CD4, CD25, and FOXP3. HALO software was used to analyze whole-slide images. The correlation between two factors was assessed using Spearman analysis. The prognostic value of factors was evaluated using Kaplan-Meier curves and Cox regression. Results A significant positive correlation was observed between Treg infiltration in tumor tissues and plasma EBV DNA levels (r = 0.3428, p = 0.02). Higher Treg infiltration was significantly associated with poorer progression-free survival (PFS) (p = 0.03) and was an independent risk factor for NPC progression (p = 0.045). CD25 expression was positively correlated with plasma EBV DNA levels (r = 0.3229, p = 0.03). Furthermore, increased Treg infiltration was negatively correlated with peripheral CD8+ T cells (r=-0.3556, p = 0.006). The proportion of peripheral CD8+ T cells in patients with advanced-stage NPC was significantly lower compared to those with early stage (p = 0.02). Conclusion This study identified tumor-infiltrating CD4+CD25+FOXP3+ Tregs as an independent negative prognostic factor for NPC progression and found higher Treg infiltration positively associated with plasma EBV DNA levels.